Extraction, structural analysis, and activities of rice bran polysaccharide. (10th July 2021) - Huang, Shiyu; Huang, Gangliang
Abstract: The rice bran polysaccharide was extracted from defatted rice bran, and the optimal conditions of the experiment were determined. The chemical structure of rice bran polysaccharide was analyzed by IR and 13 C NMR. Three rice bran polysaccharide derivatives were prepared and characterized, namely carboxymethylated rice bran polysaccharide, phosphorylated rice bran polysaccharide, and acetylated rice bran polysaccharide. It showed that the phosphorylated rice bran polysaccharide had good activity. Abstract : Extraction, structural analysis, and activities of rice bran polysaccharides were studied.